Safety and efficacy of MitraClipTM therapy in patients with severely impaired left ventricular ejection fraction: results from the German transcatheter mitral valve interventions (TRAMI) registry - Geis, Nicolas; Katus, Hugo; Bekeredjian, Raffi (European journal of heart failure, 2018)
Aims The aim of the present study was to assess the safety and efficacy of percutaneous mitral valve repair using the MitraClip™ device in patients with severely reduced systolic left ventricular (LV) function. Methods and results Among 777 MitraClip™ implantations included in the German mitral valve registry, we identified 256 patients suffering from severely reduced LV function [ejection fraction (EF) <30%] in whom successful percutaneous mitral valve repair was performed. Procedural safety, efficacy, and 1-year outcome was compared with 241 patients with preserved LV function (EF >50%) and 280 patients presenting with an EF 30-50% prior to MitraClip™ therapy. High procedural success rates, low periprocedural complication rates, and low residual mitral regurgitation grades at discharge were achieved throughout all groups. In-hospital mortality was low and comparable in all groups. After 1 year, mortality rates were 24.2% (EF <30%), 17.3% (EF 30-50%), and 18.9% (EF >50%). Major adverse cardiac or cardiovascular event rates were 29.7% (EF <30%), 24.4% (EF 30-50%), and 23.5% (EF >50%). Procedural failure was the main predictor for mortality in EF <30% patients (hazard ratio 10.38; 95% CI 3.71-29.02). Improved clinical symptoms were observed in the majority of patients in all groups. Thus, 69.5% of EF <30% patients improved by one or more New York Heart Association functional class. Compared with patients with preserved LV function, this is a significantly larger proportion (EF >50%: 56.8%; P < 0.05). Moreover, quality of life, being very poor at baseline, improved distinctively in severe heart failure patients. Conclusion In patients with severely reduced systolic LV function undergoing MitraClip™ therapy, procedural safety, efficacy, and clinical improvement after 1 year are comparable to patients with preserved LV function.
Im Titel ist "TM" hochgestellt
Online publish-ahead-of-print: 18 August 2017
Gesehen am 27.04.2018